2004
DOI: 10.1038/sj.onc.1207041
|View full text |Cite
|
Sign up to set email alerts
|

Csk defines the ability of integrin-mediated cell adhesion and migration in human colon cancer cells: implication for a potential role in cancer metastasis

Abstract: Progression of human colon cancer is often associated with elevated expression and activity of the Src family tyrosine kinase (SFK). SFK is ordinarily in equilibrium between inactive and primed states by a balance of negative regulatory kinase Csk and its counteracting tyrosine phosphatase(s), both of which act on the regulatory C-terminal tyrosine of SFK. To evaluate the contribution of the regulatory system of SFK in cancer progression, we here modulated the equilibrium status of SFK by introducing wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Our results showing that Rack1's inhibition of Src activity promotes E-cadherin-mediated cell-cell adhesion and inhibits the invasive properties of HT-29 cells (Figure 1) are consistent with those of Rengifo-Cam et al (2004) showing that overexpression of the Src inhibitor carboxylterminal Src kinase (Csk) increases cell-cell adhesion mediated by E-cadherin and decreases the invasive properties of both HT-29 and HCT15 colon carcinoma Figure 6 Rack1 blocks the HGF-induced scatter of epithelial cells by regulating E-cadherin endocytosis. Sub-confluent cultures of Rack1-depleted (a) or Rack1-transfected HT-29 cells (b, c) were serum starved overnight and treated with HGF (50 ng/ml) for 4 h. Rack1-depleted cells (a) were fixed and stained with 0.2% crystal violet and analyzed by phase-contrast microscopy.…”
Section: Discussionsupporting
confidence: 79%
“…Our results showing that Rack1's inhibition of Src activity promotes E-cadherin-mediated cell-cell adhesion and inhibits the invasive properties of HT-29 cells (Figure 1) are consistent with those of Rengifo-Cam et al (2004) showing that overexpression of the Src inhibitor carboxylterminal Src kinase (Csk) increases cell-cell adhesion mediated by E-cadherin and decreases the invasive properties of both HT-29 and HCT15 colon carcinoma Figure 6 Rack1 blocks the HGF-induced scatter of epithelial cells by regulating E-cadherin endocytosis. Sub-confluent cultures of Rack1-depleted (a) or Rack1-transfected HT-29 cells (b, c) were serum starved overnight and treated with HGF (50 ng/ml) for 4 h. Rack1-depleted cells (a) were fixed and stained with 0.2% crystal violet and analyzed by phase-contrast microscopy.…”
Section: Discussionsupporting
confidence: 79%
“…Inhibitory antibodies to ␣ v or ␤ 1 integrins restored the accumulation of E-cadherin at cell/cell contacts, linking the defects in cell/cell adhesion to enhanced integrin signaling. Similarly, increasing endogenous Src activity in HT29 cells enhanced integrin activation and disrupted cell/cell contacts (40). Because silencing of Rap1GAP exhibited effects similar to those of Src activation, we examined whether Src activity is altered by Rap1GAP depletion.…”
Section: Discussionmentioning
confidence: 99%
“…The profound alterations in cell morphology observed in Rap1GAP-depleted cells were reminiscent of those of Src activation in colon cancer cells. Overexpression of activated Src or activation of endogenous Src disrupted cell/cell adhesion through enhanced cell/ matrix adhesion (2,40). We reasoned that the increase in matrix adhesion conferred by silencing of Rap1GAP could be associated with increased Src activity.…”
Section: Silencing Of Rap1gap Expression Increases Rap Activitymentioning
confidence: 99%
“…Over-expression of a kinase-deficient Csk leads to activation of SFK (22)(23)(24). To confirm this in our system, CskR222 with Arg replacing Lys-222 was tagged by CFP and co-expressed in COS1 cells with Cbp-YFP.…”
Section: Fig 4 Fret Images Of Cbp-yfp and Cfp-csk In Living Cellsmentioning
confidence: 99%
“…Because Cbp is exclusively localized at lipid rafts, this indicator should be useful for monitoring SFK signaling originating from lipid rafts, such as EGF and T-cell receptors, and cell adhesion signaling. The progression of some human cancers is associated with the elevated expression and activity of SFK (41)(42)(43), and it has been suggested that the metastatic activity of cancer cells in particular can be defined by the status of their SFK activity (24). If an indicator that precisely reflected this status could be designed, it would be very useful for screening drugs that decrease the deregulated activity of SFK.…”
Section: Monitoring Of Sfk Activation With a Single-molecule Fretmentioning
confidence: 99%